Information society and pedagogy of the oppressed from the perspective of critical political philosophy - Khavina, Irina; Chebakova, Yuliia; Derpak, Olena; Tytarenko , Nataliia; Kharchenko, Serge (Interacción y Perspectiva, 2024)
The history of humanity is characterized by the existence of oppressive devices that, in the political, economic, social and cultural spheres, marginalize individuals and communities, preventing the enjoyment of their human rights, in accordance with their immanent dignity. In this sense, critical political philosophy has endeavored to reflect, from the philosophical programs of modernity: liberalism, contractualism and anarchism, among others, on the necessary conditions for overcoming the forms of oppression that subject the human person to a life of calamity and poverty, while naturalizing or invisibilizing their suffering. The objective of this research was to discuss the meaning and possibilities of Paulo Freire’s pedagogy of the oppressed in the context of the information society in the 21st century. In order to develop this discussion, a dialectical hermeneutic methodology was used, within the framework of the postulates of critical political philosophy. It is concluded that, considering the current information society, Freire’s ideas are still relevant to promote a more just and equitable world through education, as a previous phase to any practice of action to transform reality.